Budget Management for the Maintenance of the Sirah Pulau Padang-Pampangan Road (Study at the Ogan Komering Ilir Regency Public Works and Spatial Planning Office) - Gustina, Meri Widiya; Nisyak, Hoirun (Open Access Indonesia Journal of Social Sciences, 2019)
This research is motivated by the poor implementation of the maintenance of the Sirah Pulau Padang-Pampangan road, the maintenance activities have not reached the target and the condition of the road is badly damaged. This study aims to determine the management of the maintenance budget for the Sirah Pulau Padang-Pampangan road for the 2017 Fiscal Year at the Public Works and Spatial Planning Office of Ogan Komering Ilir Regency. The research method used in this study is a qualitative method. Data collection techniques carried out through observation, in-depth interviews and documentation. The theory used in this study is the principles of financial management according to Juli Sarlima, where financial management can be seen from five dimensions, namely Transparency, Efficient, Effective, Accountable and Participatory, and analysed through management aspects, namely Planning, Organizing, Implementing and Responsibility. Based on the results of research in the field shows that Transparency, Efficient, Effective, Accountable and Participatory has not been done well. The conclusion of this research is that the management of budget road maintenance for the Sirah Pulau Padang-Pampangan roads in the 2017 fiscal year is not going well. This research suggests that management of budget works well: 1) Standard Operational Procedure (SOP) for Road Maintenance activities needs to be made, 2) the need for a place for the community to participate and be involved in planning, implementation of supervision, 3) preparation of Financial Statements and Reports Accountability must be clear and detailed.